Face‐to‐Face Communications Is Powerful, Postdigital Communications Tool. Issue 2 (September 2017) - Egan, John
Abstract : In Malcolm Gladwell's first book, The Tipping Point, he asked, and answered, a number of provocative questions about change, including why word‐of‐mouth communications continues to be so powerful.